Reframing Stakeholder Influence: A Review of Heterogeneous Stakeholder Mobilization and Corporate Responsiveness in the Era of Digital Activism - Ahembang; Agustina, Selvi (International Journal of Business, Marketing, Economics & Leadership (IJBMEL), 2026)
This qualitative literature review explores how digital activism is transforming stakeholder influence and corporate responsiveness. Contrary to traditional models emphasizing unified collective action, recent evidence reveals that heterogeneous stakeholders now mobilize through fragmented yet emotionally resonant digital narratives. This form of "heterogeneous convergence" enables diverse publics to exert pressure on firms despite lacking organizational coherence. Drawing from contemporary cases such as #MeToo and #DeleteUber, the review highlights how digital platforms facilitate dynamic stakeholder engagement, enabling rapid reputational impacts. The findings suggest that organizations must adapt to increasingly polyphonic and contested stakeholder environments, where legitimacy is shaped not by static engagement models but by real-time digital responsiveness. This review contributes to stakeholder theory by integrating digital mobilization dynamics and calls for expanded theoretical and empirical research into digitally mediated stakeholder influence